CONSUMPTIVE CULTURE AMONG STUDENTS: CONTRIBUTIONS OF SOCIAL MEDIA MARKETING, SOCIAL PRESSURE, FINANCIAL MANAGEMENT, AND SHOPEE GAMIFICATION - Anisyah Bahar; Dewi Widyaningsih; Robby Andika Kusumajaya (Universitas Nusa Cendana, 2026)
This study examines the role of social media marketing, social pressure, financial management, and gamification in influencing the consumptive culture of students at STEKOM University in Semarang. The study focuses on active students who have a Shopee account and have made a transaction within the last three months. Using purposive sampling, 60 respondents were selected as the research sample. This research adopts a quantitative approach with an explanatory research design, and the data were analyzed using multiple linear regression with the assistance of SmartPLS 4.0. The results indicate that social media marketing, social pressure, financial management, and gamification have a positive and significant influence on students’ consumptive culture, both individually and simultaneously. These findings suggest that digital marketing exposure, social influence, and interactive platform features can encourage higher levels of consumption among students. However, this study is limited to active students of STEKOM University in Semarang with a relatively small sample size, which may limit the generalizability of the findings to other student populations. The study highlights the importance of strengthening financial literacy and increasing consumer awareness as key strategies to control excessive consumption behavior amid the growing influence of digital marketing and social pressure. The findings also provide insights for stakeholders to develop ethical and responsible marketing practices as well as appropriate regulatory strategies to reduce excessive consumptive behavior among students. Keywords: Social Media Marketing; Financial Management; Gamification; Consumptive Culture